2011
DOI: 10.1088/0004-637x/743/1/71
|View full text |Cite
|
Sign up to set email alerts
|

A Very Large Array Survey of Radio-Selected SDSS Broad Absorption Line Quasars

Abstract: We have built a sample of 74 radio-selected broad absorption line quasars from the Sloan Digital Sky Survey Data Release 5 (SDSS DR5) and Faint Images of the Radio Sky at Twenty Centimeters (FIRST), along with a well matched sample of 74 unabsorbed "normal" quasars. The sources have been observed with the NRAO Very Large Array/Expanded Very Large Array at 8.4 GHz (3.5 cm) and 4.9 GHz (6 cm). All sources have additional archival 1.4 GHz (21 cm) data. Here we present the measured radio fluxes, spectral indices, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 30 publications
4
62
1
Order By: Relevance
“…The bipolar wind model proposed by Punsly (1999a,b) was used by Ghosh & Punsly (2007) to explain the polar BAL QSOs found by Zhou et al (2006): in this model the BAL outflow would be aligned with the polar axis, while the relativistic jet would be nested inside of it. Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The bipolar wind model proposed by Punsly (1999a,b) was used by Ghosh & Punsly (2007) to explain the polar BAL QSOs found by Zhou et al (2006): in this model the BAL outflow would be aligned with the polar axis, while the relativistic jet would be nested inside of it. Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 92%
“…Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 92%
“…Becker et al (2000) find a LoBALQ fraction of ≃0.5 in the FIRST BALQ sample, compared to ∼0.1 found in SDSS samples that are dominated by RQ BALQs. DiPompeo et al (2011) report that RL BALQs are typically viewed at larger angles relative to the radio-jet axis compared to RL nonBALQs. This supports the interpretation of αUV as an inclination angle indicator, where a redder αUV implies a larger angle, since the radio-jet axis is likely to be perpendicular to the symmetry plane of the system.…”
Section: Comparison Between Rl and Rq Balqsmentioning
confidence: 98%
“…Becker et al (2000) first used the radio emission spectral index to derive the jet orientation of BAL QSOs, and noted that this can lie in wide range of possible angles. After these works, different authors presented detailed studies about larger samples of radio-loud BAL QSOs, from which they reported a variety of possible orientations for the outflow, but also a variety of possible morphologies and ages for the radio source (Montenegro-Montes et al 2008;DiPompeo et al 2011;Bruni et al 2012Bruni et al , 2013). This does not suggest a scenario that would be clearly referable to one of the proposed models.…”
Section: Introductionmentioning
confidence: 99%